(untitled) (Journal of Hama University, 2022)
The present research aimed at knowing the relationship between satisfaction about body image and psychological hardiness among a sample of second grade students of public secondary schools in Hama city, and knowing the significance of differences among the members of the study sample in satisfaction about body image and psychological hardiness, which may be due to the (Sex and specialization) variables. The study sample consists of (130) students: (71) male and female students of scientific students, and (59) male and female of theoretical students. The study tools were a scale to measure the satisfaction about body image, and a scale to measure the psychological hardiness, and both scales were prepared by the researcher. The most important findings of Search: • There were correlation statistically positive significant between the scores of students on the scale of satisfaction about body image and scores on a scale of psychological hardiness. • There were differences between the mean scores of students on the scale of satisfaction about body image due to the sex variable favor for the male students. • There were not differences between the mean scores of students on the scale of satisfaction about body image due to the specialization variable. • There were differences between the mean scores of students on the scale of psychological hardiness due to the sex variable favor for the male students. There were not differences between the mean scores of students on the scale of psychological hardiness due to the specialization variable.